A practical guideline for T1 reconstruction from various flip angles in MRI. Issue 4 (December 2016) - Sandmann, Constantin; Hodneland, Erlend; Modersitzki, Jan
A fast and robust method for T 1 estimation in MRI is the so-called variable flip angle technique. We introduce a novel family of T 1 reconstruction methods from data acquired with various flip angles and propose a family member which combines the robustness of a nonlinear- with the computational advantages of a linear reconstruction. The constructed family contains the most common approaches for T 1 estimation, namely a linear and a nonlinear approach. A general sensitivity analysis for arbitrary members of the family is established. Advantages of the optimized reconstruction are demonstrated on phantom- as well as real data, showing improvements of up to 24% as compared with the linear method. As a further means to stabilize T 1 estimation, spatial stabilization methods are compared. We demonstrate on phantom and on real data that improved results can be obtained if not only T 1 but also a second unknown M 0 in the reconstruction is stabilized.